Cost benefit analysis and the social time preference rate to estimate social discount rate in the Czech republic - Franc, Petr; Tetřevová, Liběna (Univerzita Pardubice, 2010)
The choice of the discount rate is a crucial issue for evaluating projects with longterm impacts. The paper deals with a calculation of a social discount rate for the Czech Republic based upon the Social Time Preference Rate (STPR), from which perspective the critical components of the STPR are: the elasticity of the marginal utility of consumption, the growth rate of per capita real consumption, and mortality based utility discount rate. Estimates turn out to be 1.36; 2.9 and 1.31% respectively yielding an overall figure of 5.25 %.
Keywords: social discount rate; Czech republic; cost benefit analysis